Canonical wnt signaling activity in early stages of chick lung development - Moura, Rute S. (2014)
Wnt signaling pathway is an essential player during vertebrate embryonic development which has been associated with several developmental processes such as gastrulation, body axis formation and morphogenesis of numerous organs, namely the lung. Wnt proteins act through specific transmembrane receptors, which activate intracellular pathways that regulate cellular processes such as cell proliferation, differentiation and death. Morphogenesis of the fetal lung depends on epithelial-mesenchymal interactions that are governed by several growth and transcription factors that regulate cell proliferation, fate, migration and differentiation. This process is controlled by different signaling pathways such as FGF, Shh and Wnt among others. Wnt signaling is recognized as a key molecular player in mammalian pulmonary development but little is known about its function in avian lung development. The present work characterizes, for the first time, the expression pattern of several Wnt signaling members, such as wnt-1, wnt-2b, wnt-3a, wnt-5a, wnt-7b, wnt-8b, wnt-9a, lrp5, lrp6, sfrp1, dkk1, β-catenin and axin2 at early stages of chick lung development. In general, their expression is similar to their mammalian counterparts. By assessing protein expression levels of active/total β-catenin and phospho-LRP6/LRP6 it is revealed that canonical Wnt signaling is active in this embryonic tissue. In vitro inhibition studies were performed in order to evaluate the function of Wnt signaling pathway in lung branching. Lung explants treated with canonical Wnt signaling inhibitors (FH535 and PK115-584) presented an impairment of secondary branch formation after 48 h of culture along with a decrease in axin2 expression levels. Branching analysis confirmed this inhibition. Wnt-FGF crosstalk assessment revealed that this interaction is preserved in the chick lung. This study demonstrates that Wnt signaling is crucial for precise chick lung branching and further supports the avian lung as a good model for branching studies since it recapitulates early mammalian pulmonary development.